LINC00460 Hypomethylation Promotes Metastasis in Colorectal Carcinoma - Zhang, Hui; Lu, Ya; Wu, Jianzhong; Feng, Jifeng (Frontiers in Genetics, 2019)
Epigenetic alterations and aberrantly expressed lncRNAs are pervasive in colorectal cancer (CRC) tumorigenesis. DNA methylation could control lncRNA expression and play an important role in tumor initiation and progression. However, the DNA methylation that regulates lncRNAs in CRC remains poorly characterized. In our research, we integrated dysregulated expression and methylation of lncRNAs between colorectal tumor and adjacent mucosa tissues from TCGA database. With the use of this strategy, LINC00460, the most frequently epigenetically activated, was identified and further verified in the CCLE and GEO databases. Patients with high expression of LINC00460 are prone to metastasis and are associated with poor prognosis. Abnormally expressed LINC00460 could be used as an independent prognostic risk factor for disease-free survival. Knockdown of LINC00460 promotes colon cancer cell invasion and migration in vitro. In summary, our results suggest that DNA methylation-regulated LINC00460 could promote CRC metastasis and serve as a potential therapeutic target for CRC.